PEMBERDAYAAN MASYARAKAT DESA SUMUR DEWA DALAM PEMBUATAN JAMU PEGAL LINU SEBAGAI MINUMAN PENINGKAT IMUNITAS BERBASIS POTENSI LOKAL - Madhani, Rhaina Aprilia; Asih, Devi Mutia; Anjelina, Septina; Harpepen, Andi (CV. Kalimasada Group, 2025)
This community service program aims to empower the residents of Sumur Dewa Village, Selebar Subdistrict, Bengkulu City in producing traditional jamu, particularly jamu pegal linu, as an immune-boosting drink based on local potential. The program was initiated in response to the declining interest among younger generations in traditional herbal medicine due to perceptions of its bitter taste and lack of visual appeal. To address these issues, the program adopted the Participatory Action Research (PAR) method, actively involving the community in every stage of the program—from planning and implementation to evaluation. The activities included education on the benefits of jamu and local herbal plants, training in the hygienic preparation of jamu pegal linu, attractive label and packaging design, and product marketing strategies. The results showed increased community knowledge and skills in formulating and packaging traditional jamu, along with growing interest in developing herbal businesses as an alternative source of income. This program contributes not only to the preservation of local wisdom but also to improving public health and economic well-being.